RABANI ( Reaktor Baru Wudhu Masa Kini) : Sistem Daur Ulang Air Wudhu yang Syar’i Berbasis Neo - Ema Cahyaningrum; Rinaldi Yunita Suci; Emi Cahyaningrum (Jurnal DinamikA, 2020)
Indonesia is the country with the largest adherents of Islam in the world. The number of adherents of Islam is around 212.5 million people or about 80% of the total population. With the number of mosques in Indonesia around 731,096 buildings in 2013. Every Muslim (adherent of Islam) before praying always cleanses certain body parts commonly called ablution so that it is estimated that the use of water for ablution in a day is around 1.8 million m3. The dry season that occurred in the last few months has caused many areas to experience a clean water crisis. The use of water must be carried out optimally. Islam teaches how to be frugal and fair as taught in the apostles' Sunnah. Therefore, there is a need for a system designed to recycle used ablution so that it can be reused into ablution water. RABANI uses the NEO method (membrane based zeolite, electrocoagulation and ozonation) nanofiltration. The combination of several methods of water purification will increase the effectiveness of water purification so that better quality water is produced. This system produces output products in the form of clean water that is suitable for reuse for the purification process.Keywords: Water ablution, ozonizasi, referring